Evaluation of drought and salinity tolerance potentials of different soybean genotypes based upon physiological, biochemical, and genetic indicators - Alzahrani, Yahya (Frontiers in Plant Science, 2024)
The present study has evaluated different soybean genotypes to understand the salt and drought tolerance mechanisms based on physiological traits (photosynthesis, stomatal conductance, chlorophyll, and cell membrane stability), antioxidant enzymes (superoxide dismutase, catalase, and peroxidase), reactive oxygen species (H2O2 and O2•−), osmolytes (glycine betaine, proline, and Na+/K+), plant water relations (relative water content, water potential, and solute potential) and expression of related genes (GmCAT1, GmPOD1, GmSOD, GmP5CS, GmNHX1, GmAKT1, GmDREB1, and GmARF1). The experiment was conducted in a two-factorial arrangement using randomized complete block design (RCBD) with genotypes as one factor and salt, drought, and control treatments as the other factor. All physiological traits, relative water content, and water potential decreased significantly in all soybean genotypes due to individual and combined treatments of drought and salt stress, with significantly less decrease in soybean genotypes G4620RX, DM45X61, and NARC-21. Besides that, the activity of antioxidant enzymes, production of ROS, accumulation of osmolytes, solute potential, and Na+/K+ ratio were increased significantly in all soybean genotypes under salt and water deficit conditions. As a whole, the soybean genotypes G4620RX, DM45X61, and NARC-21 showed the maximum enzymatic activity with less increase in ROS and Na+/K+ in addition to a high accumulation of osmolytes and an increase in solute potential. Correspondingly, the genotypes exhibiting high physiological and biochemical tolerance to drought and salt stresses showed the high expression of genes imparting the stress tolerance. Moreover, correlation, heatmap, and principal component analysis further confirmed the varying physiological and biochemical responses of all soybean genotypes under individual and combined applications of drought and salinity stresses. Overall, the present study confirmed that plants opt for the integrated physiological, biochemical, and genetic approaches to counteract the harmful effects of environmental stresses.